The Loyalties of E. Herbert Norman - Lyon, Peyton V. (Labour / Le Travail, 1991)
Reviews the life and work of Canadian diplomat E. Herbert Norman, who died by suicide during the Cold War after being hounded for years as a suspected agent of the Soviet Union (the US Senate had recently reopened its investigation). Concludes that Norman was not a Soviet agent nor was he disloyal, despite his communist sympathies while a student at Cambridge University in the 1930s. The report, which was commissioned by the Canadian government, is based on ministerial records, RCMP files, Norman's personal correspondence, interviews, and a literature review. Includes two appendices.
Keywords: CANADA. Dept. of External Affairs; CANADA. International Trade Tribunal; CANADA. Ministry of International Trade; Canada; Communism; NORMAN; E. Herbert; 1909-1957; SOVIET Union; SPIES; TOTALITARIANISM